RANCANG BANGUN KONTROL MONITORING LAMPU RUNWAY EDGE MENGGUNAKAN POWER LINE CARRIER - M. Syafiq Jain; Albert Panjaitan; Wahyu Kurniawan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to design and build a control and monitoring system for runway edge lights using Power Line Carrier (PLC). This system is designed to overcome the limitations of manual methods in inspecting runway lights, which are time-consuming and labour-intensive, especially in airport environments with large areas. The system uses an ESP8266 microcontroller, a PZEM-004T sensor module for monitoring electrical parameters, and a Power Line Adapter as the data transmission medium. Test results indicate that the system can transmit and receive data over a distance of ±70 metres with an average response time of 7–10 seconds. The sensor can also detect voltage and current with an error rate below 5%, demonstrating the system's accuracy and reliability. As a result, the system enhances the efficiency and effectiveness of technicians in monitoring runway edge light conditions and has the potential for further development in broader applications within the fields of electrical engineering and aviation.  Keywords:  Power Line Carrier, Runway Edge Light, Monitoring, ESP8266, PZEM-004T Abstrak: Penelitian ini bertujuan merancang dan membangun sistem kontrol serta monitoring lampu runway edge menggunakan Power Line Carrier (PLC) untuk mengatasi keterbatasan metode manual yang memerlukan waktu dan tenaga, khususnya di bandara dengan area luas. Sistem ini memanfaatkan mikrokontroler ESP8266, modul sensor PZEM-004T untuk pemantauan parameter listrik, serta Power Line Adapter sebagai media transmisi data. Hasil pengujian menunjukkan bahwa sistem mampu mengirim dan menerima data hingga jarak ±70 meter dengan waktu respons rata-rata 7–10 detik, sementara sensor mendeteksi tegangan dan arus dengan tingkat kesalahan di bawah 5%, menandakan keakuratan dan keandalan sistem. Dengan demikian, sistem ini dapat meningkatkan efisiensi dan efektivitas teknisi dalam memantau kondisi lampu runway edge, serta memiliki potensi pengembangan untuk aplikasi lebih luas di bidang kelistrikan dan transportasi udara. Kata kunci: Power Line Carrier, Runway Edge Light, Monitoring, ESP8266, PZEM-004T